2022
DOI: 10.1021/acs.jpca.2c01156
|View full text |Cite
|
Sign up to set email alerts
|

Chiral-Induced Spin Selectivity in Capacitively Coupled Molecules

Abstract: The chiral-induced spin selectivity (CISS) effect is usually associated with electrons passing through chiral molecules. There are a number of experiments where external electrical fields rearrange electrons inside otherwise isolated molecules, allegedly also generating spin polarization of the molecule. There are theoretical suggestions of pairs of molecules generating spin polarizations in each other due to fluctuating electrical dipoles. This paper critically theoretically evaluates such spin-dependent char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Numerous experimental observations show that chiral molecules interact enantiospecifically with magnetized surfaces and that chiral molecules can imprint magnetization onto ferromagnets. These experiments have spurred a new effort in theoretical developments aimed at identifying the nature of electronic spin exchange between chiral molecules and metal surfaces. , Cuniberti and co-workers used spin-polarized DFT to examine the spin-dependent DOS at molecule-ferromagnet interfaces and showed that the interfacial states are locally spin-polarized but remain singlet states globally, i.e., broken spin symmetry manifests at chiral molecule-ferromagnet substrate interfaces . These findings are corroborated by other model-based studies of chiral molecule adsorption at interfaces. …”
Section: Theoretical Understandingmentioning
confidence: 75%
See 2 more Smart Citations
“…Numerous experimental observations show that chiral molecules interact enantiospecifically with magnetized surfaces and that chiral molecules can imprint magnetization onto ferromagnets. These experiments have spurred a new effort in theoretical developments aimed at identifying the nature of electronic spin exchange between chiral molecules and metal surfaces. , Cuniberti and co-workers used spin-polarized DFT to examine the spin-dependent DOS at molecule-ferromagnet interfaces and showed that the interfacial states are locally spin-polarized but remain singlet states globally, i.e., broken spin symmetry manifests at chiral molecule-ferromagnet substrate interfaces . These findings are corroborated by other model-based studies of chiral molecule adsorption at interfaces. …”
Section: Theoretical Understandingmentioning
confidence: 75%
“…20 evaluated spin-dependent charge reorganization for molecules interacting through dipole−dipole fluctuations, and finds that the spin-polarization they manifest is quite small. 274 This latter work implies that coupling to a bath and/or vibrational degrees of freedom are needed to explain the magnitude of the effect reported experimentally. This area represents an important frontier in CISS research and could have important implications for enantioselective chemical and biochemical processes.…”
Section: Chiral Molecule Interactions and Ferromagnetsmentioning
confidence: 96%
See 1 more Smart Citation
“…9 Theoretical work also supports the idea of charge reorganization in chiral molecules being followed by spin polarization. In that case the strength of interaction is controversial with predictions for small effects, 39 as well as for large effects that are in the ball park of experiments. 40,41 By using nanoparticles which differ in their magnetic properties, we expect to induce different changes to the natural spin distribution of the protein with each type of nanoparticle.…”
Section: Discussionmentioning
confidence: 99%